Optical Solitons Possessing Beta Derivative of the Chen-Lee-Liu Equation in Optical Fibers - Yusuf, Abdullahi; İnç, Mustafa; Aliyu, Aliyu Isa; Baleanu, Dumitru (Frontiers Media Sa, 2019)
This research obtains some new optical soliton solutions with beta derivative for Chen-Lee-Liu equation (CLL) in optical fibers. Three integration schemes which are Ricatti-Bernoulli (RB) sub-ODE, generalized Bernoulli (GB) sub-ODE and generalized tanh (GT) methods are applied to reach such solutions. The constraints conditions for the existence of soliton solutions are reported. The solutions are obtained using newly introduced fractional derivative called beta derivative. Numerical simulations of some of the obtained solutions are illustrated.
Keywords: CLL; RB sub-ODE; GB sub-ODE; GT methods; beta derivative